Firstboard Sdn Bhd / Nik Anis Aziera Nik Mohd Zunaiddin - Nik Mohd Zunaiddin, Nik Anis Aziera (Faculty of Business and Management, 2023)
Industrial training is work experience required for professional development in advance of graduation. Students need to complete 24 weeks of internship program from 1st March to 15th August 2023. The internship was designed to provide practical experience in marketing, develop skills in social media marketing, content creation, market research, and hands-on experience in marketing, and help them develop skills and knowledge relevant to their career goals. During the internship, I was involved in various activities, including social media posting, content creation, and attending any event. I worked closely with my supervisor Miss Filzah Hasha and my colleagues and had the opportunity to contribute to the task. Through these experiences, I gained valuable insights into social media marketing, developed key skills such as marketing, editing, and copywriting, and learned about the day-to-day operations of Firstboard Sdn Bhd. I demonstrated strong communication skills and a willingness to learn and contribute to the team. I adapted well to the company's culture and was able to work collaboratively with other team members. Despite facing challenges such as time constraints and tight deadlines, I completed my task on time and with high quality. Overall, the internship was a positive experience for me, providing them valuable learning opportunities and professional development. The internship also gave me better understanding their career interests and aspirations and helped them identify potential career paths in marketing.